Review of the Fund's Regional Technical Assistance Centers. (Policy Papers; Policy Paper ;, 2005)
Regional technical assistance centers have become an increasingly important modality for Fund technical assistance. This review is a response to Executive Directors' calls for close monitoring and regular evaluation of their operations. The centers include, the Africa Regional Technical Assistance Centers (AFRITACs), the Caribbean Regional Technical Assistance Center (CARTAC) and the Pacific Financial Technical Assistance Center.